الإعتمادية ونقد الذات السلبي كمتغيرات وسيطة في العلاقة بين الكمالية والشره العصبي لدى طالبات جامعة الإميرة نورة بنت عبدالرحمن بالرياض - المري، سلوى بنت فهاد حماد (جامعة الزقازيق - كلية التربية, 2015)
The eating disorders represent the relationship between the psychological state of the individual, between the urge to eat or aversion for, bulimia nervosa a eating disorder characterized by intake accidental unregulated and rapid large amounts of food in a short period of time with feeling some pain in the abdomen, and that the study of disorder bulimia neivous system, especially among university students is of great importance, especially when we examine the relationship between him and many of the psychological variables self-criticism negative ,dependency and perfectionism, for the reliability and self-criticism negative, we can say that this study presented the problem in many of the questions, namely: 1- Is there a substantial relationship built bulimia nervosa and all the perfectionism and reliability of self-criticism and negative? 2- Do you neutralize raised reliability and self-criticism for the negative relationship between perfectionism and bulimia nervosa weaken the strength of that relationship? 3- Do you increase the degree of bulimia nervosa by the combined effect of both the perfectionism and reliability of self-criticism and negative? This study aimed at codifying standard reliability and self- criticism negative impact on the local environment and private environment university students,The study sample consisted of (363) female students from the University of Princess Noura girl Abdul Rahman, Riyadh and included the tools of the study were: scale reliability, thé scale of self-criticism, a list of perfectionism, and the measure of bulimia nervosa, As for the results of the study were as follows: 1- A substantial positive relationship between statistically significant and all of bulimia nervosa or reliability and negative self- criticism of the female students the university. While others have found a negative relationship is not statistically significant between bulimia nervosa and perfectionism. 2- found to neutralize the impact of reliability and self-criticism for the negative relationship between perfectionism and bulimia nervosa weaken the strength of this relationship with the university students. 3- found that increasing the degree of bulimia nervosa by the combined effect of both perfectionism and reliability of self-criticism and negative.
تهدف الدراسة إلي بحث العلاقة بين اضطرابات الأكل والحالة النفسية للفرد وخاصة الرغبة الملحة لتناول الطعام أو العزوف عنه, ويعد الشره العصبي أحد اضطرابات الأكل التي تتسم بالتناول العرضي غير المنتظم والسريع لكميات كبيرة من الطعام في فترة قصية من الوقت مع الشعور ببعض الألم في البطن, ودراسته لدى طالبات الجامعة له أهمية كبيرة وخاصة عندما ندرس العلاقة بينه وبين العديد من المتغيرات النفسية كالاعتمادية ونقد الذات السلبي والكمالية, وقد أقر التراث النفسي وخاصة الأجنبي منه بأن النساء المصابات بالشره العصبي يحتمل أن يظهرن العديد من مظاهر الشخصية الاعتمادية ونقد الذات السلبي, كما أن هناك دراسات أجنبية توصلت إلي وجود ارتباط جوهري موجب بين الكمالية والشره العصبي, ومن خلال ما سبق فإن مشكلة الدراسة تتمثل في التساؤلات التالية: هل توجد علاقة جوهرية بين الشره العصبي وكل من الاعتمادية نقد الذات السلبي والكمالية؟, هل تحييد تأثير الاعتمادية ونقد الذات السلبي عن العلاقة بين الكمالية والشره العصبي يضعف من هذه العلاقة؟ هل تزداد درجة الشره العصبي بفعل التأثير المشترك بين الكمالية وكلاً من الاعتمادية ونقد الذات السلبي؟ ولتحقيق هذا الهدف قامت الدراسة بتقنين مقياسي الاعتمادية ونقد الذات السلبي على البيئة المحلية وخاصة بيئة طالبات الجامعة, وقد عرضت الدراسات السابقة من خلال أربعة محاور وهي: دراسة عن الاعتمادية وعلاقتها ببعض المتغيرات النفسية, ومحور دراسات نقد الذات وعلاقته ببعض المتغيرات النفسية, ومحور دراسات الشره العصبي وعلاقته ببعض المتغيرات النفسية, ومحور دراسات عن الكمالية وعلاقتها ببعض المتغيرات النفسية, كما تكونت عينة الدراسة من (363) طالبة من طالبات جامعة الأميرة نورة بنت عبد الرحمن بالرياض وشملت أدوات الدراسة كلا من: مقياس الاعتمادية ومقياس نقد الذات وقائمة الكمالية ومقياس الشره العصبي, أما نتائج الدراسة فكانت كالتالي: وجود علاقة جوهرية موجبة دالة إحصائياً بين الشره العصبي وكل من الاعتمادية ونقد الذات السلبي, بينما توجد علاقة سلبية غير دالة إحصائياً بين الشره العصبي والكمالية لدى طالبات الجامعة. كما وجد أن تحييد تأثير الاعتمادية ونقد الذات السلبي عن العلاقة بين الكمالية والشره العصبي يضعف من هذه العلاقة, وأن درجة الشره العصبي تزداد بفعل التأثير المشترك بين كل من الاعتمادية ونقد الذات السلبي والكمالية.
Keywords: اضطرابات الاكل -- الحالة النفسية -- الشره العصبي -- المتغيرات النفسية -- مظاهر الشخصية -- طالبات الجامعات -- جامعة الأميرة نورة بنت عبدالرحمن -- الرياض -- الإضطرابات النفسية -- الرعاية الإجتماعية